Infección experimental por herpesvirus bovino 1 en conejas gestantes - Valera, Alejandro R. (2011)
Natural infection with Bovine herpesvirus 1 (BoHV-1) produces several clinical manifestations including conjunctivitis, respiratory signs, genital diseases and abortion. The rabbit is a good model for studying of latency, pathogenicity of BoHV-5 and other bovine herpesviruses. This study was conducted in order to analyze the response to experimental infection with BoHV-1 in rabbits during different periods of pregnancy. The results obtained could be useful for better understanding of the infection in cattle. A new method of infection was used. The rabbits developed clinical signs. The virus was recovered from nasal swabs and histological lesions were found in the analyzed samples. The humoral response was demonstrated and viral DNA was detected from the placentas. This work showed for the first time the arrival of BoHV-1 to blood after intranasal infection with the virus. It also provides a useful tool that can be used to evaluate the pathogenicity of by BoHV-1 strains, the immune response and to study viral latency and reactivation.